Laparoscopic management of CSF pseudocyst abdomen - Handa Rakesh; Harjai M; Kale R (Wolters Kluwer Medknow Publications, 2005)
Cerebrospinal fluid (CSF) pseudocyst formation is an uncommon cause of ventriculoperitoneal shunt malfunction in children. Standard management consisted of laparotomy with repositioning of the shunt and drainage of the pseudocyst. Recurrence of pseudocyst in these patients is well known and resulted in multiple laparotomies and eventually a ventriculo-atrial shunt. We managed a patient laparoscopically with drainage of the pseudocyst and repositioning of the shunt. The patient experienced no complications from the procedure, and there has been no recurrence of the pseudocyst in 2 years of follow-up. This technique has proven to be safe, with results comparable to the conventional open technique.